Minimally invasive pelvic exenteration for gynaecological malignancy: A single-centre case series and review of the literature. (July 2022) - Karkia, Rebecca; Tailor, Anil; Ellis, Patricia; Madhuri, Thumuluru; Scala, Andrea; Read, James; Perry, Matthew; Patil, Krishna; Blackburn, Adam; Butler-Manuel, Simon; Chatterjee, Jayanta
Abstract: For those with certain recurrent gynaecological cancers where primary management such as chemo-radiotherapy has failed, or in cases of recurrence following primary surgery, pelvic exenteration (PE) is considered the only curative option. Whilst initially considered a morbid procedure, improved surgical techniques, advancing technology, and nuanced reconstructive options have facilitated more radical resections and improved morbidity and mortality. Open PE remains the gold standard approach, however, minimally invasive techniques for PE may lessen morbidity whilst achieving the same oncological outcomes. The objective of this study was to assess the feasibility and safety of minimally invasive PE with a laparoscopic or robot-assisted approach. We also performed a review of the literature on robot-assisted PE which has not been widely reported for cases of recurrent gynaecological malignancy. Between 2015 and 2021 six minimally invasive PE were performed. All patients underwent extensive multi-disciplinary assessment and counselling pre-operatively. Patient characteristics, treatment indication, perioperative data, short-term complications, and histological outcomes were recorded. There were two anterior exenterations, three posterior exenterations and one total exenteration performed. The primary cancer stage varied from stage 1a-3b. Five out of six patients had pre-operative chemo-radiotherapy. The average operative time (including surgical docking) was 600 min. Mean blood loss was 400 mL and the average length of stay was eight days. Enhanced recovery practices were used where possible. There were no intraoperative complications and one major post-operative complication which was breakdown of an inferior gluteal artery perforator flap perineal reconstruction. All patients had negative margins at post-operative histopathology. All patients are alive and recurrence free at follow-up, but long-term outcome data is needed. This initial case series suggest that minimally invasive pelvic exenteration can feasibly be performed in place of open pelvic exenteration. Furthermore, our findings suggest this may be a safe alternative as we report similar findings to the existing literature, however no firm conclusions can be drawn at such an early stage. Long term follow-up data and a larger cohort study will be needed to establish non-inferiority to open PE.